2020
DOI: 10.3390/ijms21041371
|View full text |Cite
|
Sign up to set email alerts
|

Deconvolution of RNA-Seq Analysis of Hyperbaric Oxygen-Treated Mice Lungs Reveals Mesenchymal Cell Subtype Changes

Abstract: Hyperbaric oxygen (HBO) is widely applied to treat several hypoxia-related diseases. Previous studies have focused on the immediate effect of HBO-exposure induced oxidative stress on the lungs, but knowledge regarding the chronic effects from repetitive HBO exposure is limited, especially at the gene expression level. We found that repetitive HBO exposure did not alter the morphology of murine lungs. However, by deconvolution of RNA-seq from those mice lungs using CIBERSORTx and the expression profile matrices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 73 publications
(101 reference statements)
2
11
0
Order By: Relevance
“…To extend these findings, a bleomycin-induced pulmonary fibrosis mouse model was used to evaluate the effect of repetitive HBO exposure on pulmonary fibrosis. Building on our previous report (Yuan et al, 2020), we provide evidence that HBO exposure attenuates bleomycin-induced pulmonary fibrosis in mice. In vitro, HBO exposure could reverse, at least partially, transforming growth factor (TGF)-β-induced fibroblast activation.…”
Section: Introductionmentioning
confidence: 55%
See 4 more Smart Citations
“…To extend these findings, a bleomycin-induced pulmonary fibrosis mouse model was used to evaluate the effect of repetitive HBO exposure on pulmonary fibrosis. Building on our previous report (Yuan et al, 2020), we provide evidence that HBO exposure attenuates bleomycin-induced pulmonary fibrosis in mice. In vitro, HBO exposure could reverse, at least partially, transforming growth factor (TGF)-β-induced fibroblast activation.…”
Section: Introductionmentioning
confidence: 55%
“…In another report, HBO exposure reduced radiation-induced side effects including fibrosis in a rat bladder irradiation model (Oscarsson et al, 2017). Mechanistically, our recent study suggested that repetitive HBO exposure may affect biological processes in mice lungs such as response to wounding and ECM (Yuan et al, 2020). To extend these findings, a bleomycin-induced pulmonary fibrosis mouse model was used to evaluate the effect of repetitive HBO exposure on pulmonary fibrosis.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations